Sexual Health Behaviors of Deaf American Sign Language (ASL) Users - Heiman, Erica (Disabil Health J, 2015)
BACKGROUND: Little is known about the sexual health behaviors of Deaf American Sign Language (ASL) users. OBJECTIVE: We sought to characterize the self-reported sexual behaviors of Deaf individuals. METHODS: Responses from 282 Deaf participants aged 18–64 from the greater Rochester, NY area who participated in the 2008 Deaf Health were analyzed. These data were compared with weighted data from a general population comparison group (N=1890). We looked at four sexual health-related outcomes: abstinence within the past year; number of sexual partners within the last year; condom use at last intercourse; and ever tested for HIV. We performed descriptive analyses, including stratification by gender, age, income, marital status, and educational level. RESULTS: Deaf respondents were more likely than the general population respondents to self-report two or more sexual partners in the past year (30.9% vs 10.1%) but self-reported higher condom use at last intercourse (28.0% vs 19.8%). HIV testing rates were similar between groups (47.5% vs 49.4%) but lower for certain Deaf groups: Deaf women (46.0% vs. 58.1%), lower-income Deaf (44.4% vs. 69.7%) and among less educated Deaf (31.3% vs. 57.7%) than among respondents from corresponding general population groups. CONCLUSION: Deaf respondents self-reported higher numbers of sexual partners over the past year compared to the general population. Condom use was higher among Deaf participants. HIV was similar between groups, though HIV testing was significantly lower among lower-income, less well-educated, and female Deaf respondents. Deaf individuals have a sexual health risk profile that is distinct from that of the general population.